Introducing Adobe Audition CS5.5 : learn by video. - Jago, Maxim (Peachpit Press, 2011)
"This innovative product is a focused video workshop and accompanying 48-page full-color book that will teach editors how to create, edit, and enhance audio for broadcast, film, and video, using Adobe Audition CS5.5. Users will be introduced to the Audition interface and features; get acquainted with the new Mac version of Audition, find out about switching to Audition from Adobe Soundbooth, and learn about multitrack file types and versions. The video also covers importing and managing media files, working with sound files, making music, and multitrack editing. Experienced instructor Maxim Jago presents three hours of exceptional video tutorials, complete with lesson files, assessment quizzes, and review materials. The video is wrapped in a unique interface that allows the viewer to jump to any topic and also bookmark individual sections for later review. The unique Watch-and-Work mode shrinks the video into a small window to allow the student to work alongside in Audition. Project files used in the lessons are included on the disc so viewers can practice what they have learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page.